2016
DOI: 10.2131/fts.3.167
|View full text |Cite
|
Sign up to set email alerts
|

The <i>in vivo</i> Pig-a gene mutation assay is applied to study the genotoxicity of procarbazine hydrochloride in Sprague-Dawley rats

Abstract: -The Pig-a gene is well-known to encode a key enzyme essential in the biosynthesis of glycosylphosphatidylinositol (GPI), which attaches CD molecules (Cluster differentiation), such as CD55 and CD59, to red blood cells (RBCs) membranes. In this study, the blood was marked with the special antigen CD45-PE (Phycoerythrin) to separate the erythrocytes from the leukocytes, then the Pig-a mutant frequency (MF) of RBCs could be investigated without pivotal antigen CD59-FITC (Fluorescein isothiocyanate), and the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Based on this mode of action, the mutagenicity of PCZ has been reliably detectable in many in vivo tests, but it has been negative using in vitro genotoxicity assays due to the complex metabolism of the drug and deficiencies in the metabolic activation systems used for in vitro testing (Bronzetti et al, 1979;Suter, 1987;Myhr, 1991;Suzuki et al, 1999). In our previous in vivo Pig-a study (Pu et al, 2016), PCZ produced weak positive results in limited testing, where we detected a maximal~2.9-fold increase in mutant erythrocytes. In this study, the leading phenotypic indicator of the Pig-a mutation, the mean RET CD59− frequency, exhibited maximal~75.6-fold and 124.6-fold increases higher than the controls in PCZtreated rats in the 3-day and 28-day studies, respectively.…”
Section: Procarbazine Hydrochloridementioning
confidence: 79%
See 1 more Smart Citation
“…Based on this mode of action, the mutagenicity of PCZ has been reliably detectable in many in vivo tests, but it has been negative using in vitro genotoxicity assays due to the complex metabolism of the drug and deficiencies in the metabolic activation systems used for in vitro testing (Bronzetti et al, 1979;Suter, 1987;Myhr, 1991;Suzuki et al, 1999). In our previous in vivo Pig-a study (Pu et al, 2016), PCZ produced weak positive results in limited testing, where we detected a maximal~2.9-fold increase in mutant erythrocytes. In this study, the leading phenotypic indicator of the Pig-a mutation, the mean RET CD59− frequency, exhibited maximal~75.6-fold and 124.6-fold increases higher than the controls in PCZtreated rats in the 3-day and 28-day studies, respectively.…”
Section: Procarbazine Hydrochloridementioning
confidence: 79%
“…Although the two test chemicals in our study, PCZ and EC, have been investigated previously in similar integrated studies as well as assays measuring single genotoxicity endpoints, including Pig‐a gene mutation (Phonethepswath et al, ; Bemis et al, ; Labash et al, ; Stankowski et al, ; Pu et al, ; Revollo et al, ), the data reported herein allow comparisons between the responses for multiple genotoxicity endpoints as a function of two commonly employed treatment regimens (short‐term, 3‐day and subchronic, 28‐day studies). In addition to conducting multiple genotoxicity assays, analyses were made to collect data for hematology, clinical chemistry, organ weight, and other general toxicity indicators.…”
Section: Discussion and Summarymentioning
confidence: 99%